Pengaruh Personality Traits Dan Performance Politics Terhadap Turnover Intention : Studi Kasus PT Paiho Indonesia - Handayani, Sri; Rismawati, Rismawati; Sari, Endah Murtiana (Journal of Innovative and Creativity, 2026)
The high level of turnover intention has become a significant issue in human resource management as it greatly affects the sustainability of an organization. Therefore, it is necessary to understand the factors that influence employees’ intentions to leave their jobs, both from individual and organizational perspectives. This study employs a quantitative approach with a sample of 200 respondents selected using purposive sampling. Data were collected through a questionnaire using a Likert scale and analyzed using SPSS version 25, including validity, reliability, and classical assumption tests to ensure the feasibility of the model. The results show that personality traits have a positive and significant effect on turnover intention. This indicates that differences in individual characteristics influence employees’ tendencies in making decisions. In addition, performance politics also has a positive and significant effect on turnover intention, indicating that perceptions of unfairness and political practices in performance appraisal can increase employees’ intention to leave. Simultaneously, both independent variables have a significant effect on turnover intention, with a coefficient of determination of 23.4%. These findings emphasize the importance of managing employee personality traits and implementing a transparent and objective performance appraisal system to reduce turnover intention within the organization.